ADAPTATION INTO ISLAMIC EDUCATION 4.0: AN APPROACH TO REDESIGNING A SUSTAINABLE ISLAMIC EDUCATION IN THE POST PANDEMIC ERA - As'ad, Mahrus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
The unpresendented presence of Pandemic Covid 19 in the beginning of 2020 has almost paralyzed the world of global education, including Indonesia’s Islamic education as one of the biggest Islamic education systems in the world. Anticipating the possibility of similar incidents in the future, the Indonesia’s Islamic education needs to redesign its learning approach in order to create a new learning model that is more resilient, and meet the needs and the demands of Industri 4.0: Education 4.0. Unlike the conventional approache having been used so far, this new desired approach departs from a paradigm that places the students at the center of learning with the involvement of the use of on-line classes to explore them to the fullest. Philosophically, there is a resemblance of Education 4.0 orientation to the Islamic education’s concept of ‘cradle-to-grave learning’, which emphasizes the creation of life-long learners and teachers to enable them to play positive and constructive roles in today work environment and in the innovative society in general. Using the descriptive-analytical method, this paper seeks to examine the the urgency and the readiness of the Indonesia’s Islamic Education to tansform into education 4.0 and its crusial challenges in facing this demand.